Blue's Clues & You: Halloween Party! - Ordas, Emi (New York, NY : Random House Childrens Books, 2021)
Magenta doesnt have a costume, and its Halloween night! Play Blues Clues to figure out what Magenta should dress as for Halloween.
"Blues clues & you"--Cover.
Keywords: Blue (Fictitious character) -- Juvenile fiction; Dogs -- Juvenile fiction; Halloween -- Juvenile fiction; Parties -- Juvenile fiction; Fiction; Juvenile works